Analisis Pengaruh Likuiditas Akuntansi Kombinasi Bisnis pada PT XL Axiata Tbk - Elisabeth Meidiana Tyasningwuri; Nasywa Adhe Kurhan Salsabila; Desi Sulistya Damayanti (Universitas 45 Surabaya, 2024)
business combination is an event or transaction in which a company as an acquirer gains control over one or more companies. The purpose of this study was to determine how the effect of accounting liquidity on PT Xl Axiata Tbk before and after the implementation of the business combination in 2011-2014. This study collected secondary data from the Indonesia Stock Exchange using a descriptive quantitative research approach. The results of the analysis show that after the business combination, the company's performance as shown by the liquidity ratio increased rapidly. To achieve long-term goals, the business combination of PT XL Axiata Tbk with PT AXIS Telekom Indonesia is expected to increase the company's value.